Implementasi Algoritma Genetika Untuk Menentukan Solusi Pada Optimisasi Nonlinier - Hery Andi Sitompul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2014)
Determination of a set solution of nonlinear optimization problem is a complicated task,by that meansthe an exact method or technique is necessary. Genetic Algorithm is one of the most searching method or technique that has developed in the last fewdecade. Finding a set solution of nonlinear optimization problem with Genetic Algorithm technique is put into effect by considering parameter of objective function like as chromosome of living organisms, all living organisms whose have the best fitness will be survived and has ever evolution and reproduction an offsprings as a newgeneration.These generation certainly has have better fitness. By considering that an objective function as a fitness value thus optimum value will be obtained at the moment of specific generation full filled theterminating criteria. Chromosome of population in these generation will be represent a set optimum solution of nonlinier optimization.